Degradation of Polycyclic Aromatic Hydrocarbon from hazardous waste landfill leachate using Photo-Fenton process - Saleh Hoddin, Muhamad Amirul Hafiz (Universiti Teknologi PETRONAS, 2017)
Landfill leachate have been found that it is one of source of harmful organic matters called Polycyclic Aromatic Hydrocarbons (PAH). The releasing of leachate to the nearby rivers from the landfills without proper treatment are hazardous as PAH can contribute to various health problems to living things. Photo-Fenton process are known for its effectiveness in treating wastewater as it can remove organic matters and sometimes inorganic matters by oxidation process through hydroxyl radicals reaction. Wastewater that undergo Photo-Fenton shown significant COD removal